Prenatal diagnosis and postnatal management of congenital mesoblastic nephroma: A case report and literature review - Zhang, Xiaoxiao; Zhang, Huijing; Wang, Shuang; Gao, Yangxu; Liang, Li; Yang, Huixia (Frontiers in Pediatrics, 2022)
Background: Congenital mesoblastic nephroma (CMN) is a rare renal tumour in children, the most common kidney tumour in the neonatal period. It can be divided into three types, classical, cellular and mixed. Case presentation: A 31-year-old Chinese woman had no apparent foetal abnormality in regular prenatal care during the first and second trimesters. At 33 weeks of gestation, a solid mass in the right kidney was noted with echoes similar to liver and hypervascularity. It grew larger during late pregnancy. The infant was transferred to have a radical nephrectomy on the 9th day after birth. The postoperative histopathological result indicated classical CMN. Conclusion: CMN could be detected prenatally, mainly during late pregnancy. The postnatal outcome is good.